2021
DOI: 10.1002/alz.057487
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of increased regional amyloid uptake in patients with subthreshold global amyloid levels

Abstract: Background Although the standardized uptake value ratio (SUVR) method is objective and simple, cut‐off optimization using global SUVR values may not reflect focal increased uptake in the cerebrum. The present study investigated clinical and neuroimaging characteristics according to regionally increased β‐amyloid (Aβ) uptake and global Aβ status. Method We recruited 973 patients with Alzheimer's disease ‐related cognitive impairment (ADCI). All patients underwent neuropsychological tests and 501 18F‐florbetaben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is important to note that CSF-based Aβ estimates showed up to 10% higher than Aβ-PET-based estimates in people without dementia, suggesting that preclinical and prodromal AD may be more prevalent than previously estimated [44 ▪ ]. In line with this, a study revealed that participants with focally increased amyloid-PET signals, even in subthreshold global Aβ levels, showed AD patterns of neuroimaging and neuropsychological features [45], therefore more attention should be drawn to focal increased Aβ uptake in addition to global Aβ status. As the research criteria for the diagnosis of probable AD have been revised [46], amyloid-PET imaging is getting importance in clinical trials.…”
Section: Amyloid-petmentioning
confidence: 71%
“…It is important to note that CSF-based Aβ estimates showed up to 10% higher than Aβ-PET-based estimates in people without dementia, suggesting that preclinical and prodromal AD may be more prevalent than previously estimated [44 ▪ ]. In line with this, a study revealed that participants with focally increased amyloid-PET signals, even in subthreshold global Aβ levels, showed AD patterns of neuroimaging and neuropsychological features [45], therefore more attention should be drawn to focal increased Aβ uptake in addition to global Aβ status. As the research criteria for the diagnosis of probable AD have been revised [46], amyloid-PET imaging is getting importance in clinical trials.…”
Section: Amyloid-petmentioning
confidence: 71%